An Evaluation of Zakat Distribution Alignment with Maqashid al-Shariah: A Case Study of BAZNAS Malang City - Ahmad Djalaluddin; Lempang Hasibuan; Yousf Faraj Hadiri (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2026)
Purpose:This study aims to evaluate the extent to which zakat distribution implemented by BAZNAS Malang City aligns with the five dimensions of Maqashid al-Shariah: protection of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-ʿaql), lineage (hifz al-nasl), and wealth (hifz al-mal).Design/Methodology:A quantitative descriptive-evaluative approach was employed using structured questionnaires distributed to 278 zakat recipients (mustahik). The data were analyzed using mean score interpretation based on predetermined Likert-scale interval categories to assess the level of alignment with maqasid principles.Findings:The findings indicate that zakat distribution is generally aligned with the principles of Maqashid al-Shariah. The strongest alignment is observed in the dimensions of wealth and religion, suggesting that zakat programs significantly contribute to both economic empowerment and spiritual development. In contrast, the protection of lineage demonstrates relatively lower alignment, highlighting the need to strengthen family-oriented initiatives and enhance long-term program sustainability.Practical Implications:These findings suggest that zakat institutions can function not only as charitable distributors but also as strategic agents of holistic social welfare development when guided by maqasid-based evaluation frameworks. The study recommends strengthening productive and transformative zakat programs to ensure sustainable empowerment and long-term social impact for mustahik.Originality/Value:This study contributes original value by empirically evaluating zakat distribution using a comprehensive five-dimensional Maqasid al-Shariah framework at the institutional level of BAZNAS Malang City. It measures beneficiary-based outcomes across all maqasid objectives through structured quantitative indicators. The study bridges normative maqasid theory with measurable institutional performance.